Production and characterization of xanthan gum by bacterial isolates - Kure J.T; Ahmadu, U; Gana, M; Salubuyi, S. B.; Ijah U. J. J (Covenant Journal of Physical and Life Sciences, 2022)
Xanthan gum is a microbial polymer synthesised by a plant pathogen of the Xanthomonas genus. Due to its rheological characteristics and water solubility, it is of enormous commercial significance and has been utilized as a thickening and stabilizing agent in a variety of industries. In this work, the potential for synthesizing xanthan gum in Xanthomonas species isolated from black rot spotted tomatoes, peppers, mango, and bananas was investigated. After washing the leaves in saline solution, a tenfold dilution was made, and aliquots (1 ml) were placed on a nutrient agar plate and incubated for 48 h at 25 °C. Gram staining was made on colonies that appeared yellow. An emulsification test was carried out on bacteria that were gram-negative rods. Potential xanthan gum producers include isolates displaying yellow colonies, gram-negative rods, and stable emulsions on carbon-enriched media. These requirements were satisfied by eight (61.5 %) of the isolates tested. Biochemical analysis of the isolates indicated that they were Xanthomonas species, and they were coded appropriately (BX2, BX3, PX4, MX6, PX7, MX8, TM9, TX11). The molecular analysis of the best two isolates (TM9 and BX3) revealed that they were Xanthomonas campestris and Stenotrophomonas maltophilia. After 96 h of incubation, Xanthomonas campestris and Stenotrophomonas maltophilia were the most effective xanthan gum producers, generating 2.10 g/l and 1.63 g/l of xanthan gum, respectively. The apparent viscosity (AV), emulsification index (IE24), scanning electron microscopy (SEM), thermogravimetric analysis (TGA), and differential scanning calorimetry (DSC) were used to characterize the xanthan gums produced. The findings indicated little or no differences between commercially synthesized xanthan gum and produced xanthan gum. However, xanthan gum from Stenotrophomonas maltophilia has a higher apparent viscosity (660.6 mPas) that is above those of Xanthomonas campestris (526.1 mPas) and commercial xanthan gum (411.3 mPas), respectively. The gums showed structural similarities and exhibited good thermal stability. These findings indicate that Xanthomonas species are viable options for xanthan gum production.